SMART LAMP BERBASIS ARDUINO NANO YANG DIKONTROL OLEH APLIKASI MOBILE - Tamrin, Tamrin; Yanti, Indri; Pauzan, Muh (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Arduino nano based smart lamp has been made. The BH1750 light sensor is used as input for light intensity from the environment and the RTC DS3231 as input for time, date and day. The smart lamp is controlled via a mobile application. MITApp Inventor platform is used to build mobile applications. In the application, there are three modes, namely manual mode, sensor-based automatic and scheduling mode. Mode selection is operated through a mobile application, communication between the smartphone and the device uses Bluetooth communication. In manual mode, the user can press the ON or OFF button at any time. In sensor-based automatic mode depends on the light intensity conditions around the device, if the light intensity is < 10 lux then the lamp will turn on automatically, if the value is > 10 lux then the lamp will be turned off automatically. In the scheduling mode, users can also turn ON and turn OFF the lamp on a scheduled basis, such as when the lights are turned on at 18:00 WIB and turned off at 06:00 WIB. The test results show that in manual mode the system works as expected, in automatic mode the sensor also works as intended. In scheduled mode, the smart lamp works according to the set time by user